Pre-intervention characteristics in weight loss participants scoring positive and negative for food addiction. Issue 4 (2018) - Schulte, Trina Aguirre; Koehler, Ann; Bowman, Rebecca (Becci); Pierce, Kayla; Bloodgood, Molly; Kreman, Rebecca
No abstract available